(untitled) (Revista de História da UEG (REVHIST), 2020)
This text intends to analyze the posture adopted by the officials of the Assembly of Belém in relation to the Capuchins of Piety. The city councilors used the artifice of accusations and denunciations against these religious in several letters sent to the Metropolis, during the first half of the 18th century. These complaints mainly referred to the question of indigenous labor and its supposed monopoly by religious. In addition to the accusations related to the misappropriation of indigenous people, the missionaries were also denounced for their moral and religious conduct, considered illegal by the Assembly officials. Keywords: Belém Assembly. Capuchins of Piety. Colonial Amazon. Missions.